2006
DOI: 10.1007/s10162-006-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Receptor 2 is Protective Against Noise-Induced Hair Cell Death: Studies in CX3CR1+/GFP Mice

Abstract: Acoustic trauma was recently shown to induce an inflammatory response in the ear characterized by rapid entry of macrophages in the spiral ligament. The current study seeks to elucidate the mechanisms involved in summoning macrophages to the cochlear lateral wall and the role macrophages play in noiseinduced injury or repair. CCL2 and its primary receptor, CCR2, are the most widely validated effectors of monocyte chemotaxis in vivo. CCL2 -/-and CCR2 -/-mice have been used extensively in studies of monocyte act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 29 publications
(33 reference statements)
2
55
0
Order By: Relevance
“…Abundant leukocyte recruitment was observed in all three groups of bone marrow chimeras. monocyte migration in brain and spinal cord, appear not to be critical cues for monocyte migration in the ear (Sautter et al 2006).…”
Section: Discussionmentioning
confidence: 91%
“…Abundant leukocyte recruitment was observed in all three groups of bone marrow chimeras. monocyte migration in brain and spinal cord, appear not to be critical cues for monocyte migration in the ear (Sautter et al 2006).…”
Section: Discussionmentioning
confidence: 91%
“…CX3CR1 GFP/GFP male mice were acquired from The Jackson Laboratory and bred with C57Bl/6 females to produce CX3CR1 GFP/+ mice. These heterozygous mice have been used in previous studies of inner ear macrophages, which indicated that CX3CR1 GFP/+ mice have normal macrophage function in the inner ear and express GFP exclusively in macrophages (Hirose et al 2005;Sautter et al 2006;Sato et al 2008Sato et al , 2010.…”
Section: Cx3cr1 Gfp/+ Micementioning
confidence: 99%
“…This influx of monocytes initiates hours after cochlear injury and peaks at approximately 2–7 days after the initial damage (Fredelius, Rask-Andersen, 1990; Hirose et al, 2005; Tornabene et al, 2006; Wakabayashi et al, 2010). The infiltrated cells have been identified in various anatomic sites of the cochlea, with a marked accumulation in the spiral ligament, the scala tympani and the spiral limbus (Du et al, 2011; Hirose et al, 2005; Miyao et al, 2008; Sautter et al, 2006; Tornabene et al, 2006). In the spiral ligament, immune cells are present primarily in the region around fibrocytes (Hirose et al, 2005; Tornabene et al, 2006).…”
Section: Introductionmentioning
confidence: 99%